The relationship between isometric force-time characteristics and dynamic performance: a systematic review - Lum, Danny (2020)
The purpose of this article was to review the data on the relationship between multi-joint isometric strength test (IsoTest) force-time characteristics (peak force, rate of force development and impulse) and dynamic performance that is available in the current literature. Four electronic databases were searched using search terms related to IsoTest. Studies were considered eligible if they were original research studies that investigated the relationships between multi-joint IsoTest and performance of dynamic movements; published in peer-reviewed journals; had participants who were athletes or active individuals who participate in recreational sports or resistance training, with no restriction on sex; and had full text available. A total of 47 studies were selected. These studies showed significant small to large correlations between isometric bench press (IBP) force-time variables and upper body dynamic performances (r2 = 0.221 to 0.608, p < 0.05) and significant small to very large correlation between isometric squat (ISqT) (r2 = 0.085 to 0.746, p < 0.05) and isometric mid-thigh pull (IMTP) (r2 = 0.120 to 0.941, p < 0.05) force-time variables with lower body dynamic performances. IsoTest force-time characteristics were shown to have small to very large correlations with dynamic performances of the upper and lower limbs as well as performance of sporting movements (r2 = 0.118 to 0.700, p < 0.05). These data suggest that IsoTest force-time characteristics provide insights into the force production capability of athletes which give insight into dynamic performance capabilities.